Situation Report: Poland, 29 October 1962 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. More on Polish Reaction to Cuba Quarantine Sergei Romanowski in Warsaw Rapacki Visit to Yugoslavia Postponed Peasants' Resistance to Expropriation Course of African, Asian, and South American Economists Polish Shipping